METHODOLOGICAL ASPECTS OF TEACHING RUSSIAN - Usmanova Svetlana Negmatovna (American Journals Publishing, 2023)
The article discusses the approaches and methods used in the methodology of teaching the Russian language. One of the most widely used methods is linguodidactics, which in recent years has shown itself in the effectiveness of the educational approach. The main methods of the theory of language learning are analyzed: didactic and methodological methods. In educational institutions, the use of these techniques is associated with the development of information technology, which is of great importance in the development of the student's personality, intellectual abilities, and moral education of students.
Keywords: linguodidactics, methodology vocabulary, competence, communication.